Leg amputation following intramuscular injection of iron dextran in a 32 year old woman - Gloria Shalviri; Kheirollah Gholami; Naghmeh Javidnikou (Research Center for Rational Use of Drugs (RCRUD), 2015)
To inform healthcare professionals of a rare serious reaction leading to leg amputation following intramuscular injection of iron dextran and report comments for preventing such reactions.A case of leg amputation following intramuscular injection of iron dextran reported to Iranian Pharmacovigilance Center was reviewed. Patient and reaction data was collected by assessing the reported yellow card, patient chart review and interviewing with patient and physicians. World Health Organization definition for serious reactions was used to determine the seriousness of the reaction. Naranjo algorithm was used to determine probability scale. The probability of the reaction was determined based on questionnaire of Schumock et al. The studied case is classified as a rare and serious but preventable reaction induced by intramuscular injection of iron dextran in a 32 year old woman. The probability of the reaction is appeared to be "probable" based on Naranjo algorithm. It seems that Iron dextran could cause serious and life threatening adverse effects. It is necessary for healthcare professionals to be informed of such rare but serious reaction in order to apply preventive actions.